2009
DOI: 10.1016/j.peptides.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral transfer of vasoactive intestinal peptide (VIP) gene inhibits rat aortic and pulmonary artery smooth muscle cell proliferation

Abstract: Vasoactive intestinal peptide (VIP), a 28 amino acid peptide, has been shown to inhibit proliferation of vascular smooth muscle cells. In previous studies VIP and VIP analogues have been used to study the effects of the peptide on vascular smooth muscle cell function. In this study an adenovirus encoding the VIP gene was used to investigate the mechanism of the antiproliferative action of VIP in vascular smooth muscle cells. Primary cultures of aortic and pulmonary artery smooth muscle cells from male Sprague-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Hypoxia causes fibroblast [ 33 ] and pulmonary arterial smooth muscle proliferation [ 4 ] in an NFAT-dependent manner. On the other hand, it has been shown that hypoxia decreases lung VIP levels in rats [ 34 ] and VIP can cause relaxation and inhibition of vascular smooth muscle cell proliferation [ 26 ]. The property of VIP to inhibit NFATc3 in mouse pulmonary artery smooth muscle both in vivo and in culture, and the finding that NFAT activity is enhanced in vivo in pulmonary artery smooth muscle from VIP KO mice, strongly supports the concept that VIP and NFAT are inextricably intertwined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia causes fibroblast [ 33 ] and pulmonary arterial smooth muscle proliferation [ 4 ] in an NFAT-dependent manner. On the other hand, it has been shown that hypoxia decreases lung VIP levels in rats [ 34 ] and VIP can cause relaxation and inhibition of vascular smooth muscle cell proliferation [ 26 ]. The property of VIP to inhibit NFATc3 in mouse pulmonary artery smooth muscle both in vivo and in culture, and the finding that NFAT activity is enhanced in vivo in pulmonary artery smooth muscle from VIP KO mice, strongly supports the concept that VIP and NFAT are inextricably intertwined.…”
Section: Discussionmentioning
confidence: 99%
“…These studies then suggest a link between VIP and NFAT. VIP has been described, with respect to the pulmonary circulation, merely as a vasodilator of pulmonary vessels [ 21 25 ] but also suppresses vascular smooth muscle cell proliferation [ 26 ]. These actions are mediated primarily by reducing intracellular Ca 2+ via activation of the cAMP/protein kinase A (PKA) pathway [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…VIP gen deletion resulted in an over expression of genes to promote smooth muscle cell proliferation and inflammation [22], another finding to underline the key role of VIP in PAH. Additional evidence for the key role of VIP in PAH is the observation that the transfection of VIP gene sequences to aortic and PSMC from rats resulted in a decreased cell proliferation and in an increased intracellular production of cyclic AMP [23].…”
Section: Vip In Pulmonary Hypertensionmentioning
confidence: 99%
“…Replication incompetent adenovirus are attractive vehicles for in vitro and in vivo gene transfer based on several key attributes, including ease of production to high titer, infection of both dividing and non-dividing cells (Kirshenbaum et al, 1993;Lemarchand et al, 1992;Quantin et al, 1992;Marini et al, 1995;Conget and Minguell, 2000;Shinoura et al, 2000;St Hilaire et al, 2009;Hong et al, 2009;Feng et al, 2008), and systemic stability (Brody and Crystal, 1994). However, the virus has several important limitations, one of which is the nonspecific tissue distribution after in vivo gene transfer and/or the inefficient gene transfer into cells lacking in one of the adenovirus receptors, coxsackievirus and adenovirus receptor (CAR) (Bergelson et al, 1997;Miller et al, 1998;Pickles et al, 1998;Zabner et al, 1997).…”
Section: Introductionmentioning
confidence: 99%